Preliminary Data on the Safety of Phytoene- and Phytofluene-Rich Products for Human Use including Topical Application - Fabien Havas; Shlomo Krispin; Antonio J. Meléndez-Martínez; Liki von Oppen-Bezalel (Journal of Toxicology)
The colorless carotenoids phytoene and phytofluene are comparatively understudied compounds found in common foods (e.g., tomatoes) and in human plasma, internal tissues, and skin. Being naturally present in common foods, their intake at dietary levels is not expected to present a safety concern. However, since the interest in these compounds in the context of many applications is expanding, it is important to conduct studies aimed at assessing their safety. We present here results of in vitro cytotoxicity and genotoxicity studies, revealing no significant cytotoxic or genotoxic potential and of short- and long-term human in vivo skin compatibility studies with phytoene- and phytofluene-rich tomato and Dunaliella salina alga extracts, showing a lack of irritancy or sensitization reactions. These results support the safe use of phytoene- and phytofluene-rich products in human topical applications.